Functionalized graphene oxide for anti-VEGF siRNA delivery: preparation, characterization and evaluation in vitro and in vivo. Issue 33 (10th April 2017) - Ren, Lulu; Zhang, Yifan; Cui, Chunying; Bi, Yanzhao; Ge, Xu
Abstract : GO–PLL–SDGR/VEGF-siRNA inhibits tumor growth as a tumor targeting delivery system. Abstract : RNA interference (RNAi) treatment is a promising and effective method for gene therapy in cancer treatments. Small interference RNA (siRNA) plays an indispensable role in the process of RNAi, resulting in gene silencing. However, naked siRNA has difficulty in crossing the cell membrane and can easily be deactivated by enzymolysis. An ideal carrier is required for siRNA delivery to overcome these disadvantages. In this study, GO–PLL–SDGR (poly-l -lysine and Arg-Gly-Asp-Ser functionalized graphene oxide), a graphene oxide (GO)-based carrier that can actively target tumors, was prepared and characterized. Results of an agarose gel retardation assay indicated that 10 μg of GO–PLL–SDGR could load 1 μg of VEGF-siRNA. It was found that the release of VEGF-siRNA from GO–PLL–SDGR/VEGF-siRNA was slow and sustained. The efficiency of gene silencing and the tumor growth inhibitory activity of GO–PLL–SDGR/VEGF-siRNA were investigated both in vitro and in vivo by RT-qPCR, ELISA and an S180 tumor-bearing mice model. RT-qPCR and ELISA assays revealed that the expressions of VEGF-mRNA and VEGF protein were down-regulated by 40.86% and 51.71%, respectively, in vitro . In vivo, the Cy-3 labeled VEGF-siRNA was observed to assemble in tumor tissues, and the tumor inhibitory rate of GO–PLL–SDGR/VEGF-siRNA was 51.74%. What's more, GO–PLL–SDGR exhibited low cytotoxicity in the MTT assay. As all the evidence shows above, GO–PLL–SDGR could be used in siRNA delivery systems as a non-viral tumor targeting carrier.